Transformation of Urban Tourism in Bali Through the Tri Hita Karana Philosophy as a Model of Sustainable Development - Ni Luh Adiani; Nyoman Diah Utari Dewi; Ni Putu Tirka Widanti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The transformation of urban tourism in Bali has intensified following the significant increase in tourist arrivals in the post-COVID-19 period. The rapid growth of urban tourism in Denpasar and Badung contributes substantially to the regional economy, yet it also generates considerable pressure on environmental carrying capacity, urban infrastructure, and the socio-cultural dynamics of local communities. This study aims to examine the transformation of urban tourism in Bali through the philosophy of Tri Hita Karana as a model for sustainable tourism development. A descriptive qualitative approach was employed, using in-depth interviews, field observations, and policy documentation analysis as primary data collection techniques. The findings reveal that the integration of Tri Hita Karana values into urban tourism governance remains partial. The palemahan dimension is reflected in environmental policies such as restrictions on single-use plastics, although it has not been holistically embedded in urban planning frameworks. The pawongan dimension highlights limited community participation in strategic decision-making processes, while the parahyangan dimension is mainly accommodated through the preservation of cultural rituals without formal integration into spatial and urban development policies. This study emphasizes the urgency of strengthening Tri Hita Karana-based governance to ensure that Bali’s urban tourism develops not only as a globally competitive destination but also as a culturally harmonious and environmentally sustainable model in the long term. Keywords: Urban Tourism, Tri Hita Karana, Sustainable Development, Tourism Governance, Bali